POLA BIMBINGAN ORANG TUA DALAM MENDIDIK PERILAKU KEAGAMAAN REMAJA DI KELURAHAN NENDAGUNG PAGAR ALAM SELATAN - silahudin silahudin (UIN Fatmawati Sukarno Bengkulu, 2016)
This study raised the issue of Parental Guidance Pattern in Educating Religious Behavior of Teens in Nendagungvillage of South Pagar Alam. This study used qualitative research methods to understand the phenomenon of what isexperienced by research subjects. The Techniques of data collection used were interviews, observation and documentation.From the results of this study indicate that the parental guidance pattern in educating religious behavior by guidingadolescent teenager has been running well, but not maximized yet, it can be seen in daily practice for every parent thatalready provides guidance and examples to each of their children in daily life like good character toward the family betweenparents and children, among children with their parents, between moral life with peers and neighbors who already guidedby parents in in Nendagung village of South Pagar Alam, guiding teens to have good manners indeed to be with feelingand heart, because adolescence is an age that is highly vulnerable and have very high ego. Inhibiting factors of parents ineducating their religious behavior of teenagers in in Nendagung village of South Pagar Alam arising from environmentaland social effects of technological advances require the guidance of the family especially the parents as the closest personwith the growth and education for teenagers at home.Moral is awareness of one’s soul to deeds without consideration ofthe mind first. Therein lies the role of parents in shaping the personality, characters and morals of teens. Parents shouldhave a role and a high knowledge, all of it can be obtained in a religious activity. The moral of teenagers formed or notdepends on the responsibility, understanding and knowledge that exist in the elderly. Parents have a responsibility toguide, nurture and maintain their children, so it is expected that the teenagers have good morals.